A community outbreak of legionnaires' disease associated with a cooling tower in Vic and Gurb, Catalonia (Spain) in 2005 (2009)
We report the investigation of a communityacquired outbreak of Legionnaires’ disease. An epidemiological, environmental, and meteorological investigation was undertaken. Fifty-five cases were reported in October and November 2005. The exposure occurred in a large area, with 12 cases (21.8%) located between 1,800 and 3,400 metres from the source. Water sample cultures showed that Legionella pneumophila serogroup 1 (Lp-1) was present in five cooling towers in two industrial locations in Gurb (plants A and B). Two Lp-1 strains were recovered from plants A and B, but only Lp-1 strains from plant A showed a pulsed-field gel electrophoresis (PFGE) profile identical to those obtained from three of the cases. Inspection of the cooling towers in plant A revealed inadequate maintenance. Weather conditions in October 2005, with mostly high temperatures and high humidity, together with the flat terrain could have been favouring factors. This study showed a community outbreak from a cooling tower as a common source in a large area. Climate and terrain could explain the dissemination of contaminated aerosols.